Cervical cancer screening uptake in Arab countries: a systematic review with meta-analysis - Hebatalla Abdelmaksoud Abdelmonsef Ahmed; Mohammed Hamdi Abbas; Hussein Awad Hussein; Rehab Salah Fathy Nasr; Amira Ahmed Lashen; Heba Khaled; Ahmed Azzam (BMC Cancer)
Abstract Background Cervical cancer, though one of the most common cancers affecting women globally, holds immense potential for prevention through screening. Therefore, we conducted this meta-analysis to assess the rate of cervical cancer screening in Arab countries and identify barriers among those who did not participate. Methods A comprehensive search was conducted from January 1st to June 1st,2024, including all observational studies that reported cervical cancer screening uptake in any Arab country. A meta-analysis was performed using a random-effects model to estimate the pooled prevalence, and sensitivity analyses were conducted to test the robustness of the findings. The study followed PRISMA guidelines. Results This meta-analysis, covering 55 studies and 204,940 Arab women, found an overall cervical cancer screening uptake rate of 18.2% (95% CI: 13.9–23.6), with sensitivity analysis confirming the reliability of this estimate. Country disparities were evident, with Bahrain having the highest uptake at 44.1%, while Somalia had the lowest at 8.9%. Among women who underwent screening, the majority were ever-married (94.7%) and held positive attitudes towards screening (91.0%). Barriers to screening were common among women who did not participate, with the most frequent reasons being a lack of information (25.1%), the misconception of feeling healthy (24.5%), fear of the procedure (19.3%), and feelings of embarrassment (13.2%). Additionally, women who were screened had lower perceived barrier scores (SMD = -0.466) and higher perceived benefits scores (SMD = 0.379) than those who were not (p < 0.05). Conclusion This meta-analysis reveals a low overall cervical cancer screening uptake (18.2%) among Arab women. Key barriers such as lack of information, fear, the misconception of feeling healthy, and embarrassment hinder uptake. This alarmingly low rate underscores the urgent need for targeted interventions to address these barriers and promote awareness of early detection’s life-saving potential.